p-DIVISIBILITY OF CO-DEGREES OF IRREDUCIBLE CHARACTERS. Issue 1 (7th February 2021) - BAHRAMIAN, ROYA; AHANJIDEH, NEDA
Abstract : For a character [STIX]x1D712 of a finite group G, the co-degree of [STIX]x1D712 is [STIX]x1D712^c(1)=[G:ker[STIX]x1D712]/[STIX]x1D712(1) . We study finite groups whose co-degrees of nonprincipal (complex) irreducible characters are divisible by a given prime p .